2014
DOI: 10.1523/jneurosci.2276-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intrinsic Connectivity in the Central Nucleus of the Mouse Inferior Colliculus

Abstract: The inferior colliculus (IC) in the mammalian midbrain is the major subcortical auditory integration center receiving ascending inputs from almost all auditory brainstem nuclei as well as descending inputs from the thalamus and cortex. In addition to these extrinsic inputs, the IC also contains a dense network of local, intracollicular connections, which are thought to provide gain control and contribute to the selectivity for complex acoustic features. However, in contrast to the organization of extrinsic IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 75 publications
2
41
0
Order By: Relevance
“…By maintaining intact connections in the IC commissural pathway, our preparation now enables extended investigations of the functional topography of these excitatory and inhibitory inputs with laser-scanning photostimluation via glutamate uncaging. In this regard, our initial assessment of the functional topography of intrinsic collicular projections are in agreement with recent comprehensive studies of the development of the intrinsic IC connections in the mouse, which have shown overlapping excitatory and inhibitory domains (Sturm et al, 2014). The commissural collicular projections also appear to receive excitatory and inhibitory inputs, with at least one source of excitatory inputs originating from a homotopic contralateral collicular locus, in agreement with neuroanatomical studies (Schweizer, 1981, Ross et al, 1988, Malmierca et al, 1995, Cant, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…By maintaining intact connections in the IC commissural pathway, our preparation now enables extended investigations of the functional topography of these excitatory and inhibitory inputs with laser-scanning photostimluation via glutamate uncaging. In this regard, our initial assessment of the functional topography of intrinsic collicular projections are in agreement with recent comprehensive studies of the development of the intrinsic IC connections in the mouse, which have shown overlapping excitatory and inhibitory domains (Sturm et al, 2014). The commissural collicular projections also appear to receive excitatory and inhibitory inputs, with at least one source of excitatory inputs originating from a homotopic contralateral collicular locus, in agreement with neuroanatomical studies (Schweizer, 1981, Ross et al, 1988, Malmierca et al, 1995, Cant, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Such limitations naturally gives rise to concerns of whether the functional organization assessed in juvenile mice are applicable to adults and whether similar conditions also preserve the IC commissural connections in the adult due to maturation of structural geometries. Indeed, analysis of intrinsic IC connections during development in the mouse demonstrate profound changes for excitatory and inhibitory circuits (Sturm et al, 2014), possibly due to developmental refinements of axonal arbors or alterations to synaptic properties. Consequently, potential modifications for preserving these connections in older animals may likely be required and suitable caveats for the interpretation of data obtained in juvenile animals must be adhered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations